HUBUNGAN KEPATUHAN MINUM OBAT DENGAN KUALITAS HIDUP PASIEN TUBERKULOSIS DI RUMAH SAKIT ISLAM JAKARTA PONDOK KOPI PERIODE APRIL –MEI 2024 - Rahmat Widiyanto; Aries Meryta; Aisyah Nur Rahmawati (Jurnal Riset Kefarmasian Indonesia, 2025)
Tuberculosis (TB) is a contagious disease that remains a global health problem and is included in the Sustainable Development Goals (SDGs). This disease is caused by Mycobacterium tuberculosis, which spreads through the air and generally attacks the lungs. To this day, the disease has been difficult to adressed, partly due to patients' non-compliance in taking anti-tuberculosis drugs. The objective of this study is to investigate the relationship between medication adherence and quality of life in tuberculosis patients. The study employed an observational cross-sectional design, utilizing the ProMas questionnaire and the WHOQOL-BREF instrument, both of which have been validated for reliability and validity. The sample in this study consisted of tuberculosis patients at the DOTS Clinic of Jakarta Islamic Hospital Pondok Kopi, East Jakarta, from April to May 2024 who met the inclusion criteria. The results showed that medication adherence was moderately high, with 41 (54.67%) patients falling into this category. Patient quality of life in domain 1 (physical) was in the moderate category for 43 (57.33%) patients, domain 2 (psychological) was in the moderate category for 20 (26.67%) patients, domain 3 (social relationships) was in the moderate category for 43 (57.33%) patients, and domain 4 (environmental) was in the moderate category for 40 (53.33%) patients. The results of the analysis of the relationship between the ProMAS questionnaire and the WHOQOL-BREF showed that only domain 2 on psychological factors had a significant effect on medication adherence with a p-value of 0.021. It can be concluded that, only domain 2 had a significant effect on medication adherence among tuberculosis patients.